PENGUATAN AKHLAK DAN KARAKTER ANAK USIA DINI MELALUI PROGRAM PESANTREN KILAT DI RA MUSLIMAT NU MLANGEN - Sidiq Hidayatullah; Dahlia Dahlia; Muhammad Amin (Institut Agama Islam Syubbanul Wathon Magelang, 2025)
This community service activity was implemented to fill the schedule during the month of Ramadan, taking the form of a Short Pesantren Program (Pesantren Kilat) at RA Muslimat NU Mlangen, Desa Menoreh. The program aimed to solidify the understanding of Islamic principles and to strengthen and develop good character (akhlak) among early childhood students. Initial observation revealed constraints such as a limited number of teachers, insufficient facilities, and a lack of varied learning activities. To address these issues, an innovative program was designed, blending religious education, practical skills, and character building. The activity took place from March 21 to March 23, 2025, involving active collaboration from RA teachers, students from the Syubbanul Wathon Magelang Islamic College, and parents, with 70 early childhood students participating. Core activities included daily worship habituation, moral education through storytelling, and Islamic creative activities. This program proved to be an effective solution for character education needs and strengthened the collaborative role of teachers, parents, and the surrounding environment in shaping a morally upright generation.